THE NURSING PROFESSION: A NOBLE AND ESSENTIAL CAREER (Лучшие интеллектуальные исследования, 2025)
Annotation. Nursing is a vital and noble profession focused on caring for individuals, families, and communities to maintain or improve health and well-being. Nurses play a crucial role in healthcare settings by providing direct patient care, administering treatments, offering emotional support, and educating patients about managing their health. The profession requires a blend of compassion, critical thinking, and scientific knowledge.